The Effect of Smartphone Usage Intensity on Students’ Learning Discipline at MTs Miftahul Ulum, East Lampung - Bahrudin; Sugiarto; Roudhotul Jannah, Siti (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the effect of smartphone usage intensity on students’ learning discipline at MTs Miftahul Ulum, East Lampung. The research employed a quantitative approach with a cross-sectional survey design. The population consisted of 164 students, with a sample of 122 respondents selected using a simple random sampling technique. Data were collected through a Likert-scale questionnaire measuring smartphone usage intensity and learning discipline. Data analysis was conducted using normality tests, linearity tests, simple linear regression, hypothesis testing (t-test), and the coefficient of determination with the assistance of SPSS.The results indicate that smartphone usage intensity does not have a significant effect on students’ learning discipline, as shown by a significance value of 0.236 (> 0.05) and a coefficient of determination of 1.2%. These findings suggest that learning discipline is not directly influenced by smartphone usage intensity, but rather by other factors such as self-control, learning motivation, and the educational environment. This study contributes novel insights by examining this relationship within the context of a madrasah, which has distinct religious characteristics. The implication of this study highlights the importance of managing smartphone use in a wise and educational manner to support the learning process.